FUNGSI SITUS PAGAR BATU DI DESA PARDOMUAN, SIMANINDO, SAMOSIR, SUMATERA UTARA - Singarimbun, Anugrah Syahputra (Humanis; Volume 12. No.3. September 2015, 2015)
Archeology studies attempting to reconstruct human culture in the past and the culture transformation in the past through materials remains of the past societies. The relics in the past basically had highly historical value. Elements of culture in the past in the this research concerning the remains of megalithic elements contained in the Pagar Batu Site, Pardomuan Village, Simanindo, Samosir, North Sumatra. The megalithic remains of the grave stone, mortar stone, manger stone, monolith, and foot washing stone. The purpose of this research is to determine the function of megalithic remains found in Pagar Batu Site and function of Pagar Batu site. Pagar Batu site was functioned as a site of worship, site of burial, and the site of settlements, whereas in the present work as remains people of  Pagar Batu Village that not used again  as well as identity indicator clan of Situmorang people. Megalithic remains as well as Pagar Batu site is is a megalithic remains as well as a site categorized as death monument because not used again such as the orginal function it was created
Keywords: megalithic remains, Pagar Batu Site, function.